Aplicación de la prisión preventiva en el Ecuador por los operadores de justicia, sin la fundamentación y motivación legal requerida en el COIP. - León Rodondi., Luis Vicente (2024)
This legal research, under the modality of curricular integration work, is titled: “Application of pretrial detention in Ecuador by justice operators, without the required legal foundation and motivation in the COIP”. The importance of developing this research topic lies in the fact that, in recent years, the precautionary measure of pretrial detention has been applied excessively and disproportionately in Ecuador. The public prosecutor’s office exercises the title of public criminal action, and they can request pretrial detention as long as there are sufficient evidence and indications of conviction that allow for proper foundation of the existence of a procedural risk, meeting all the requirements indicated in article 534 of the Comprehensive Organic Penal Code. It has been identified that, in many cases, requests for pretrial detention lack adequate foundation, and judges often apply this measure without considering the specific circumstances of the case and without reasonableness criteria. The decisions of the judicial bodies, due to ignorance or omission, do not conform to the standards of the Inter-American Human Rights System, which establish that deprivation of liberty should be an exceptional and not generalized measure. This has led to the violation of one of the most important rights after the right to life, which is individual freedom. With the information gathered in this work, the existence of arbitrary and illegal decisions in the pretrial detention orders issued by the penal guarantee judges has been evidenced. These decisions expose the accused to serve a sentence in advance, directly affecting their presumption of innocence and their integrity in the most severe way. This decontextualizes the preventive purposes pursued by this precautionary measure, which should not be configured as punitive purposes, since it does not have a real impact on reducing crime and violence. All persons are individually free, therefore, the precautionary measures that limit personal freedom must be exceptional and administered with restrictive criteria, due to the affectation of a constitutional right, and must comply with the requirements of international treaties and instruments to which Ecuador is ratified.